Children with "sensitive skin". The role of skin irritation in the development of ''atopic eczema''. - Cremer, H. (European Journal of Pediatric Dermatology, 2018)
Much importance has been attached to the role of allergy in the development of eczema in children. However, I am convinced that in children with "atopic eczema" a faulty defense barrier of the skin ("sensitive skin") is the decisive factor in the further development of skin irritation -caused by irritants that would have no effect on normal skin. This skin irritation - which is often caused by synthetic clothing, softeners and finisher - often results in the development of eczema. I therefore regard it important to advise parents of children with sensitive skin to avoid clothing that can cause irritation when in direct contact with the skin.